Examining the Knowledge Levels of Classroom Teacher Candidates about Global Warming - UYANIK, Gökhan (Journal of Computer and Education Research, 2022)
The aim of this research is to examine the knowledge levels of classroom teacher candidates about global warming. The survey model was used in the study. The sample of the study consists of a total of 324 teacher candidates studying in the Kastamonu University Faculty of Education. The research was carried out in the fall semester of the 2019-2020 academic year. Global warming knowledge scale was used as a data gathering tool. In the analysis of the data, t-test for independent groups, one-way analysis of variance (ANOVA) and Bonferroni test were used. According to the findings, it has been determined that there was a significant difference in favor of female teacher candidates according to the gender variable who have been studying at the fourth grade level. However, when the knowledge levels of classroom teacher candidates studying at different grade levels on global warming were examined, it was determined that there was a significant difference between the scores of the first grade teacher candidates and the second, third and fourth grade teacher candidates in favor of the second, third and fourth grade teacher candidates
Keywords: Alan Eğitimleri; Classroom teacher candidates; global warming; knowledge level; Other Fields of Education; 13. Climate action; 4. Education